2019
DOI: 10.1182/bloodadvances.2019000554
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of murine MLL-ENL–driven leukemia initiation changes with age and peaks during neonatal development

Abstract: MLL rearrangements are translocation mutations that cause both acute lymphoblastic leukemia and acute myeloid leukemia (AML). These translocations can occur as sole clonal driver mutations in infant leukemias, suggesting that fetal or neonatal hematopoietic progenitors may be exquisitely sensitive to transformation by MLL fusion proteins. To test this possibility, we used transgenic mice to induce one translocation product, MLL-ENL, during fetal, neonatal, juvenile and adult stages of life. When MLL-ENL was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 56 publications
0
44
2
Order By: Relevance
“…To understand the mechanistic role of these different molecular lesions, mouse models have been developed using gene editing to create transgenic mice. In parallel, patients derived samples have been used to generate xenotransplants in immunocompromised mice (PDX) [ 5 , 6 , 7 ]. These transgenic mice have helped understanding the role of the different fusions in leukemic transformation.…”
Section: Modeling Infant Leukemia: Ontogeny and Infant Amlmentioning
confidence: 99%
See 2 more Smart Citations
“…To understand the mechanistic role of these different molecular lesions, mouse models have been developed using gene editing to create transgenic mice. In parallel, patients derived samples have been used to generate xenotransplants in immunocompromised mice (PDX) [ 5 , 6 , 7 ]. These transgenic mice have helped understanding the role of the different fusions in leukemic transformation.…”
Section: Modeling Infant Leukemia: Ontogeny and Infant Amlmentioning
confidence: 99%
“…During fetal life hematopoiesis, the fetal liver supports self-renewal and differentiation of hematopoietic stem cells and multipotent progenitors (HSC/MPPs). Oncogenic events, mainly fusions, occurring in these fetal liver progenitors impact leukemia phenotype [ 5 , 7 ]. How these fusions impact transcription, disrupt transcription factor balance and promote leukemogenesis may reveal opportunities for treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the neonatal microenvironment can potentiate AMLs generated by retroviral transduction of murine HSPC with MLL-AF9 or MLL-ENL for mixed-lineage leukaemia output [ 131 ]. Furthermore, a MLL-ENL knock-in model showed that leukaemia initiates more efficiently from foetal and neonatal cells as compared to their adult counterparts, owing to younger HSPCs being more competent at activating the required oncogenic programme [ 160 ].…”
Section: The Impact Of Mll1 Fusions On Haematopoietic Developmentmentioning
confidence: 99%
“…In humanized mouse models, Horton et al could show that human cord blood (huCB) cells were more susceptible for a retroviral MLL-AF9 immortalization, whereas retrovirally transduced huBM cells failed to immortalize in vitro and did not develop leukemia in vivo [ 9 ]. Similarly, by using mouse cells and an MLL-ENL fusion transcript Okeyo-Owuor et al could demonstrate that the efficiency of MLL-ENL -driven AML changes with age with a peak shortly after birth [ 10 ]. In addition, the respective fusion partner has potential influence on leukemia development, as we and others could demonstrate its important role on the resultant phenotype: ENL exclusively led to ALL, whereas AF9 presented as AML, ALL or mixed phenotype in mouse xenograft models [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%